Hubungan Motivasi Kerja Dengan Prestasi Guru dan Karyawan di SDIT Haji Jalaluddin - Muhammad Irsyad; Zulfani Sesmiarni (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Work motivation is an important factor that influences individual performance in an organisation, including in a school environment. At SDIT Haji Jalaluddin, the relationship between work motivation and teacher and employee performance is the main focus to improve the quality of education and school operations. Work motivation can come from various sources, such as financial incentives, a conducive work environment, recognition of achievements and opportunities for professional development. Motivated teachers tend to have high enthusiasm in teaching, innovate in teaching methods, and show high dedication towards improving student learning outcomes. Similarly, motivated employees will make maximum contributions in administrative and operational tasks, thus creating an efficient and productive school environment. This study aims to identify the extent to which work motivation affects the achievement of teachers and employees at SDIT Haji Jalaluddin. Then for the principal can actively always pay attention to the development and progress that has been achieved by teachers and employees in producing good performance. The methods used include surveys and interviews to collect data on the level of motivation and individual performance. The results of the study are expected to provide strategic recommendations for school management in designing effective motivation programmes, so that the performance of teachers and employees can be continuously improved, which ultimately contributes to the achievement of the vision and mission of SDIT Haji Jalaluddin.